Hull Laundry Strike, c. 1920
1929 1918-1939 "Hull Laundry Strike, c. 1920" [T0110.jpg], 1920s Hull Laundry Strike 1920. In November 1919, the Laundries Trade Board established a guaranteed minimum wage of 28 shillings for a 48 hour week. By mid-1920, laundresses in Hull were still on the minimum rate, while workers in other towns were earning more. On June 26, the National Federation of Women Workers (NFWW) called its laundry members out on strike. The Hull Trades Council supported the strike and on July 17 helped to organise a parade through the town accompanied by local bands. Many smaller laundries managed to keep open despite the strike and the NFWW was outraged to find strike breakers being smuggled in in laundry baskets.